Failure of the Maintenance Gantry of a Metro Crossing Bridge - Vatansever, Cüneyt; YAZICI, GÖKHAN; SEÇKİN, EDİP; Alçiçek, Haluk Emre (Pergamon-Elsevier Science Ltd., 2020)
This paper investigates the failure of the underdeck maintenance gantry of the metro crossing bridge in Istanbul, Turkey on January 4, 2014, which resulted in the injury of four workers. First, a brief description of the gantry and the bridge has been provided, which is followed by the findings of the on-site investigation which involved the review of the video record of the incident, interviews with the field staff, overview of the project drawings and the investigation of the parts of the collapsed gantry. Additionally, the finite element model of the part where the collapse initiated was created and loaded in accordance with the operation procedures of the gantry during the incident. Finally, on-site investigation and finite element analysis results revealed that collapse of the gantry occurred by exceeding the shear capacity of the bolts in the connections. Moreover, the exceedance of the shear capacity was the consequence of unexpected operating practices used by the workers during the incident, which caused unforeseen shear stress concentration in the bolts.
Keywords: Underdeck Maintenance Gantry; Gantry Failure; Accident Investigation; Metro Crossing Bridge